Palmitoylation as a Functional Regulator of Neurotransmitter Receptors. (3rd April 2018) - Naumenko, Vladimir S.; Ponimaskin, Evgeni
Abstract : The majority of neuronal proteins involved in cellular signaling undergo different posttranslational modifications significantly affecting their functions. One of these modifications is a covalent attachment of a 16-C palmitic acid to one or more cysteine residues (S-palmitoylation) within the target protein. Palmitoylation is a reversible modification, and repeated cycles of palmitoylation/depalmitoylation might be critically involved in the regulation of multiple signaling processes. Palmitoylation also represents a common posttranslational modification of the neurotransmitter receptors, including G protein-coupled receptors (GPCRs) and ligand-gated ion channels (LICs). From the functional point of view, palmitoylation affects a wide span of neurotransmitter receptors activities including their trafficking, sorting, stability, residence lifetime at the cell surface, endocytosis, recycling, and synaptic clustering. This review summarizes the current knowledge on the palmitoylation of neurotransmitter receptors and its role in the regulation of receptors functions as well as in the control of different kinds of physiological and pathological behavior.